Koalisi Ornop Pasca Orde Baru: Studi tentang Jaringan Walhi dalam Kampanye Isu Hutan - Harsono, Febryandi (UI Scholars Hub, 2011)
One kind of campaign that do by lot of non-governmental organization that focus their movement on environmental issue is forestry issue campaign. Walhi as one of the biggest environmental organization in Indonesia is always powerful on doing forestry issue campaign. This campaign is held in order to show their empathy with forest problems in Indonesia nowadays. Forestry issue campaign is held to aware the government and our society that they need to save our forest is do by work alone as one organization or work together, build network with another non governmental organization in order to make some non governmental organization coalition. This coalitions’s function is to strengthen, support forestry issues that do by Walhi and another non-governmental organization.